If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = -1(4x + 4) Reorder the terms: 3 + x = -1(4x + 4) Reorder the terms: 3 + x = -1(4 + 4x) 3 + x = (4 * -1 + 4x * -1) 3 + x = (-4 + -4x) Solving 3 + x = -4 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 3 + x + 4x = -4 + -4x + 4x Combine like terms: x + 4x = 5x 3 + 5x = -4 + -4x + 4x Combine like terms: -4x + 4x = 0 3 + 5x = -4 + 0 3 + 5x = -4 Add '-3' to each side of the equation. 3 + -3 + 5x = -4 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = -4 + -3 5x = -4 + -3 Combine like terms: -4 + -3 = -7 5x = -7 Divide each side by '5'. x = -1.4 Simplifying x = -1.4
| 2z+2=3z-1 | | 0.8x+7.8=3.4 | | 4=-7y+4y | | log[14](x-70)=3-log[14]x | | 3x^2+6xy-2y^3+6=0 | | 5=-8y+5y | | 3(k-3)=15 | | 1/2*24*(88+24) | | x+4y=130 | | 1/2*18*(72+24) | | -3-2=2a+3 | | -5x+5+9x= | | 2r+3x=-4 | | 6x+6x+2+9=9x+5+2x | | 42-7u=36+u | | 6(y-5)=5y | | 8/x+1/4=5/x+1/3 | | 5x+8=8+6x | | 144x/x+3*432/x+3 | | 2+3(1-2x)=2(2+3x)-3 | | 3x+7y=1 | | 2/3r+8/r | | k/s-11=5 | | 11.5+.9=24.1 | | 5x/6+1/3(6+x)=37 | | 3n-10=25 | | 9n-13=5n+7 | | X^16=9 | | 2x-3=90 | | 2(4r-6)=2/3(12r-18) | | -7y+20=6y-6 | | 4x+15-17=16 |